Analisa Karakteristik Campuran Aspal Menggunakan Serbuk Kaca - Sucipto Sucipto; Yusra Aulia Sari (Journal of Civil Engineering and Planning (JCEP), 2021)
Pavement is a space for vehicles to operate, consisting of a composition of materials which is divided into several layers aiming to withstand the weight working on it and distribute them to the layers below. Road Pavement consists of several types, flexible pavement, rigid pavement and composite pavement. Road which is commonly used in Batam city is composite pavement, which is a combination of rigid pavement and flexible pavement. This study discusses the use of glass powder as an alternative to filler in the AC-WC pavement mixture. Waste pieces of glass that are no longer in use are destroyed until they pass through filter no. 200, pieces of glass are easily encountered because of the many furniture that uses glass as the main material. Glass waste as a filler mixture is expected to reduce the budget and reduce glass waste itself. The sample in this study consisted of 3 samples with 3 types of test, conventional asphalt with 4 samples, asphalt with a mixture of 3% glass powder filler with 3 samples, and asphalt with a mixture of 6% glass powder filler with 3 samples. Based on the laboratory tests that were conducted, asphalt that uses glass powder filler as a filler substitute meets the 2018 BinaMarga specifications with the MQ value of 637,235, VIM value of 3,829, VMA value of 18,609 and VFA value of 79,455. Based on this study it can be concluded that glass powder waste can be used as a replacement for pavement fillers.